THE VILLAGE LAW IS A GRACE FOR VILLAGE IN INDONESIA - Junaedi (Journal of Innovation Research and Knowledge, 2021)
The study in this article regarding the enactment of Law Number 32 of 2004 concerning Regional Government is the forerunner to the birth of Law Number 6 of 2014 concerning Villages which provides legal certainty to village governments to make independent efforts to advance the welfare of rural communities. Through Village-Owned Enterprises which were established using the authorized capital from the Central Government, Regency/City Governments, and community savings, they are engaged in rural resources. BUMDes provides income as dividends to the Village Government. Therefore, the birth of the village law is a blessing in itself for rural areas in Indonesia. The research was conducted with a phenomenological narrative approach. Data were collected through literature study and empirical observations. The results of the study show that with the new village law, rural development becomes even, community welfare increases through village community empowerment, village income increases with village-owned enterprises and equitable infrastructure development due to the availability of budget.